Fluorescence in situ hybridization applied to domestic animal cytogenetics - Rubes, J; Pinton, A; Bonnet-Garnier, A; Fillon, V; Musilova, P; Michalova, K; Kubickova, S; Ducos, A; Yerle, M (Cytogenetic and genome research, 2009)
The aim of this article is not to present an exhaustive review of molecular cytogenetics applications in domestic animal species, but more to illustrate the considerable contribution of these approaches in diagnostics and research in economically important species. A short presentation of the main applications of molecular cytogenetics in humans points out the domains in which it has become an essential tool and underlines the specificities attached to this species in comparison to farm animals. This article is devoted to outlining the current resources available in domestic species and to some examples of fluorescence in situ hybridization applications in the cattle, pig, horse and avian species. From a clinical point of view, these examples illustrate the advantages of FISH for the study of chromosomal abnormalities (identification, characterization and estimation of their effects). Other applications of molecular cytogenetics are also illustrated, particularly ZOO-FISH, an approach which allows the determination of chromosome homologies between species. Finally, a specific emphasis was placed on the usefulness of molecular cytogenetics for the analysis of species such as poultry, which harbour a complex karyotype.
Keywords: Female; Chromosomes, Artificial, Bacterial; Animals; ženské pohlaví; mužské pohlaví; Animals, Domestic; Male; hybridizace in situ fluorescenční; DNA Probes; hospodářská zvířata; umělé bakteriální chromozomy; zvířata; DNA sondy; In Situ Hybridization, Fluorescence